Fair-weather liberals and loyal conservatives: The effects of political ideology on the loyalty of sports fans. Issue 3 (23rd December 2019) - Soderberg, Andrew T.; Zhang, Teng; Lytle, Brad
Abstract : Purpose: Drawing on moral foundations theory, this paper aims to investigate the moral component of loyalty, a critical determinant of long-term organisational success. Design/methodology/approach: This paper contains two studies using archival data gathered from the Major League Baseball and the National Basketball Association in the USA. Findings: This paper finds empirical support for the "ideology-loyalty hypothesis" – namely, fans in more politically conservative communities are more loyal to their professional sports teams than those in more liberal ones. Originality/value: These findings contribute to a growing literature on the moral roots of organisational phenomena by providing evidence of community-level effects of political ideology on loyalty. Based on these findings, this paper suggests that when making strategic decisions (e.g. expansion into a new market), organisations need to pay attention to the political climate of the communities in which they operate (or intend to operate) to achieve and sustain organisational success.